The SF36 as an outcome measure of services for end stage renal failure. Issue 4 (December 1998) - Wight, J P; Edwards, L; Brazier, J; Walters, S; Payne, J N; Brown, C B
Abstract : OBJECTIVE: To evaluate the use of the short form 36 (SF36) as a measure of health related quality of life of patients with end stage renal failure, document the results, and investigate factors, including mode of treatment, which may influence it. DESIGN: Cross sectional survey of patients with end stage renal failure, with the standard United Kingdom version of the SF36 supplemented by specific questions for end stage renal failure. SETTING: A teaching hospital renal unit. SUBJECTS AND METHODS: 660 patients treated at the Sheffield Kidney Institute by haemodialysis, peritoneal dialysis, and transplantation. Internal consistency, percentage of maximal or minimal responses, SF36 scores, effect sizes, correlations between independent predictor variables and individual dimension scores of the SF36. Multiple regression analysis of the SF36 scores for the physical functioning, vitality, and mental health dimensions against treatment, age, risk (comorbidity) score, and other independent variables. RESULTS: A high response rate was achieved. Internal consistency was good. There were no floor or ceiling effects other than for the two "role" dimensions. Overall health related quality of life was poor compared with the general population. Having a functioning transplant was a significant predictor of higher score in the three dimensions (physical functioning, vitality, and mental health) for which multiple regression models were constructed. Age, sex, comorbidity, duration of treatment, level of social and emotional support, household numbers, and hospital dialysis were also (variably) significant predictors. CONCLUSIONS: The SF36 is a practical and consistent questionnaire in this context, and there is evidence to support its construct validity. Overall the health related quality of life of these patients is poor, although transplantation is associated with higher scores independently of the effect of age and comorbidity. Age, comorbidity, and sex are also predictive of the scores attained in the three dimensions studied. Further studies are required to ascertain whether altering those predictor variables which are under the influence of professional carers is associated with changes in health related quality of life, and thus confirm the value of this outcome as a measure of quality of care.